MANFAAT WAKAF DAN PERMASALAHANNYA - Wulandari, Dewi (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2022)
Wakaf is a special practice of worship, this is because the rewards of wakaf will continue to flow even though the wakap giver has died. So the practice of wakaf is different from other practices of worship, such as: prayer, fasting, hajj and others whose thighs are cut off when the person dies. This is in accordance with the hadith of the Prophet Muhammad that when a person has passed away, his deeds will be cut off except for three things, namely pious children who always pray for their parents, useful knowledge, charity (wakaf). Wakaf is not only intended for the benefit of religious facilities and social only but also directed to advance the general welfare by realizing the potential and economic benefits of wakaf objects. This enables the management of wakaf assets to enter the area of ​​economic activity in a broad sense as long as the management is in accordance with the principles of management and Sharia economics. Therefore, to secure wakaf property from interference by third parties that harm the interests of wakaf, it is necessary to improve Nazhir's capabilities. However, the management of wakaf in Indonesia is not optimal. The inadequate management of wakaf is influenced by several factors, including the public's understanding of wakaf, wakaf management, wakaf assets and nazdir are still lacking. For this reason, it is necessary to change the paradigm of wakaf towards productive wakaf by optimizing its potential. wakaf and then productively empower all wakaf assets in order to make an obtimal contribution to improving the quality of life of Muslims